Java EE made easy : patterns, architecture and frameworks - Karanam, Ranga; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2018)
"The list of Jargon used in Java EE is endless. For a beginner, Java EE can be overwhelming. The objective of the course is to give a big picture view of Java EE. You will understand the jargon, specifications, and patterns used in Java EE. You will understand the basic architecture of a Java EE application. You will get an overview of the patterns used in the Java EE world, grouped by the layer they are used in: front controller, view helper, composite view, context object, intercepting filter, domain model, fa(cedil)cade, DTO/VO, DAO - data access object, and service activator. You will also be introduced to terminologies like JPA, JDBC, ORM, JNDI, EJB, JTA, DTO, VO, JAXB, JAX-RS, JAX-WS, AOP and dependency injection."--Resource description page.
Presenter, Ranga Karanam.
Title from resource description page (Safari, viewed March 16, 2018).
Keywords: Java (Computer program language); Application software -- Development; Electronic books